Simultaneous Evaluation of Diagnostic Assays for Pharyngeal and Rectal Neisseria gonorrhoeae and Chlamydia trachomatis Using a Master Protocol - Doernberg, Sarah B (Clin Infect Dis, 2019)
BACKGROUND: Pharyngeal and rectal Neisseria gonorrhoeae and Chlamydia trachomatis play important roles in infection and antibacterial resistance transmission, but no US Food and Drug Administration (FDA)–cleared assays for detection at these sites existed prior to this study. The objective was to estimate performance of assays to detect those infections in pharyngeal and rectal specimens to support regulatory submission. METHODS: We performed a cross-sectional, single-visit study of adults seeking sexually transmitted infection testing at 9 clinics in 7 states. We collected pharyngeal and rectal swabs from participants. The primary outcome was positive and negative percent agreement for detection of N. gonorrhoeae and C. trachomatis for 3 investigational assays compared to a composite reference. Secondary outcomes included positivity as well as positive and negative predictive values and likelihood ratios. Subgroup analyses included outcomes by symptom status and sex. RESULTS: A total of 2598 participants (79% male) underwent testing. We observed N. gonorrhoeae positivity of 8.1% in the pharynx and 7.9% in the rectum and C. trachomatis positivity of 2.0% in the pharynx and 8.7% in the rectum. Positive percent agreement ranged from 84.8% to 96.5% for different anatomic site infection combinations, whereas negative percent agreement was 98.8% to 99.6%. CONCLUSIONS: This study utilized a Master Protocol to generate diagnostic performance data for multiple assays from different manufacturers in a single study population, which ultimately supported first-in-class FDA clearance for extragenital assays. We observed very good positive percent agreement when compared to a composite reference method for the detection of both pharyngeal and rectal N. gonorrhoeae and C. trachomatis. CLINICAL TRIALS REGISTRATION: NCT02870101.